Identification and characterization of viruses in sweet potato (Ipomoea batatas (L.) Lam.) - Jayalekshmi V S (Department of Plant Biotechnology, College of Agriculture, 2015)
The study entitled "identification and characterization of viruses in sweet potato (Ipomoea batatas (L) Lam.) was carried out at the division of crop protection, Central Tuber Crops Research Institute, Sreekariyam, Trivandrum during 2014-2015. The objective of the study was to diagnose, clone and characterize viruses implicated in mixed infections of sweet potato. Sweet potato samples with various virus infection symptoms were collected from the germplasm repository of CTCRI, Trivandrum and field samples from Bhubaneswar. Samples were screened mainly for Sweet potato feathery mottle virus ( SPFMV ), Sweet potato mild mottle virus ( SPMMV), Sweet potato leaf curl virus (SPLCV ), Sweet potato chlorotic stunt virus ( SPCSV), Sweet potato virus G (SPVG), Sweet potato virus C (SPVC), Sweet potato virus 2 (SPV2) using both genus and virus specific primers. Out of 32, 29 samples showed SPFMV infection in PCR with virus specific primers. While mixed infection by SPFMV and SPLCV was found in 15 samples. One sample was infected with SPVG along with SPFMV and SPLCV. SPMMV, SPVC, SPV2 and SPCSV screening through PCR gave negative results for all samples. PCR by virus specific primers of SPFMV and SPLCV amplifying the partial CP gave amplicons size of 411 bp and 446 bp respectively. Rather than the virus specific primers, the group specific primers Pot1/Hrp5 gave an amplicon of 1300 bp lead to the detection of SPVG. After identification, one sample each for SPFMV, SPLCV and the only sample positive for SPVG were cloned and sequenced. The sequence data was analyzed through BLAST and sequence similarity was studied. The 304 nt SPFMV sequence obtained in the study showed maximum similarity of 96% to Sweet potato feathery mottle virus isolate Fe polyprotein gene, partial cds (Accession EU021070). The 251 nt SPVG sequence obtained showed maximum similarity of 90% to sweet potato virus G isolate IS103, complete genome (AccessionKM014815). While the 418 nt SPLCV sequence obtained showed maximum similarity of 96% to Sweet potato leaf curl virus DNA A, complete sequence (Accession AF104036) and Sweet potato leaf curl isolate CTCRI TVM M1, complete genome (Accession KM 050768). The phylogenetic tree was constructed with similar sequences using phylip. Phylogenetic analysis clearly revealed that the sequences obtained in this study belongs to SPFMV for the sample S1294, SPLCV for the sample S1294, SPLCV for the sample S684 and SPVG for the sample S270 as they grouped along with their respective virus sequences used for comparison analysis. Since the diagnosis of virus infections based on symptoms is unreliable due to complicated mixed infections in sweet potato with multiple viruses and isolates, it is necessary sensitive diagnostic tests are developed region wise to confront this issue. As a prerequisite to this, virus detection and identification has to be carried out in sweet potato to determine the viruses geographically.